2019
DOI: 10.3389/fcell.2019.00253
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Regulates miR-384 Transcription During Th17 Polarization

Abstract: MicroRNAs are powerful regulators of gene expression in physiological and pathological conditions. We previously showed that the dysregulation of miR-384 resulted in a T helper cell 17 (Th17) imbalance and contributed to the pathogenesis of experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis. In this study, we evaluated the molecular mechanisms underlying the abnormal increase in miR-384. We did not detect typical CpG islands in the Mir384 promoter. Based on a bioinformatics analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Gene promoter sequences (2000 bp upstream of the start site) were extracted from the genome of Moso bamboo. The JASPAR database ( http://jaspar.genereg.net/ ) was used to predict the binding site genes of PeBBX [ 96 ]. The screening index was set to less than 1.0 E − 6 to identify the genes targeted by BBX members.…”
Section: Methodsmentioning
confidence: 99%
“…Gene promoter sequences (2000 bp upstream of the start site) were extracted from the genome of Moso bamboo. The JASPAR database ( http://jaspar.genereg.net/ ) was used to predict the binding site genes of PeBBX [ 96 ]. The screening index was set to less than 1.0 E − 6 to identify the genes targeted by BBX members.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been shown that granulocyte-macrophage CSF (GM-CSF) and TNF-α can respectively reduce the expression/production of hsa-miR-223 and hsa-miR-138 [155] , [200] ( Table 1 ). It has also been reported that upregulated activation of STAT3 in the experimental autoimmune encephalomyelitis (EAE) model is accompanied by a higher expression level of hsa-miR-384 resulting in increased differentiation of Th17 lymphocytes [201] ( Table 1 ). As mentioned in part 7.1, some target mRNAs can degrade the corresponding hsa-miRNAs [189] , [190] ( Table 1 ).…”
Section: Hsa-mirnas and Sars-cov-2-induced Interfering Factorsmentioning
confidence: 98%
“…Interestingly, IL-6-mediatated activation of STAT3 strongly induces miR-183-96-182 expression, which in turn inhibits FOXO1 in pathogenic Th17 cells. Similarly, STAT3 activation mediates the induction of miR-384 in CD4 + T cells, which reduces the expression of SOCS3, elevates the Th17/Treg ratio, and aggravates inflammation in EAE (43,81). One final example of a positive regulation of Th17 cell differentiation by miRNA is the miR-132/212 cluster.…”
Section: Mirnas In Msmentioning
confidence: 99%